1997
DOI: 10.1017/s1357729800016258
|View full text |Cite
|
Sign up to set email alerts
|

Detection of silent oestrus in dairy cows by milk temperature measurement

Abstract: Milk temperature was measured automatically during milking with a view to detecting silent oestrus in dairy cows. A total of 38 silent oestrous periods were studied, based mainly on ovulation and milk progesterone levels together with visual observation.In 78·9% of silent oestrous periods, a significant increase in milk temperature amounting to a mean of 0·6 (s.e. 0·07)°C was found, and this was highly correlated (r = 0·90) with an increased body temperature. In most silent oestrous periods increases in milk a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
3
1
1
Order By: Relevance
“…The findings of the present study also suggest that silent estrus may also occur in later cycles (cycles 4 and 5). Gil et al (1997) stated that 48% of animals displayed at least one silent estrous cycle before becoming pregnant whereas in the current experiment this was found to be the case in 59% of animals. In the present study a silent estrous cycle was defined as an animal not being observed in estrus by the trained dairy technicians during an ob-servational period or by the farm staff on their routine observations.…”
Section: Behavioral Trendscontrasting
confidence: 62%
“…The findings of the present study also suggest that silent estrus may also occur in later cycles (cycles 4 and 5). Gil et al (1997) stated that 48% of animals displayed at least one silent estrous cycle before becoming pregnant whereas in the current experiment this was found to be the case in 59% of animals. In the present study a silent estrous cycle was defined as an animal not being observed in estrus by the trained dairy technicians during an ob-servational period or by the farm staff on their routine observations.…”
Section: Behavioral Trendscontrasting
confidence: 62%
“…McArthur et al (1992) found that milk temperature increased 0.4 ± 0.1°C at estrus. Temperatures were highly variable, however, and temperature increases lasted for short periods with a mean increased time of 9 h. Gil et al (1997) reported a strong correlation between increased rectal temperature and increased milk temperature (r = 0.90) in 78.9% of 38 silent ovulations based on visual observation of standing to be mounted. Table 4.…”
Section: Variable Percent Changes At Estrusmentioning
confidence: 98%
“…The investigations which were carried out in Poland and other countries confirmed the possibility of using milk temperature values automatically registered during milking for diagnosis of oestrus in cows, early pregnancy and subclinical and acute mastitis (Ball et al, 1978;Fordham et al, 1987A,B;Fordham et al, 1988;Gil, 1988;Gil et al, 1997;Gil ert al., 2001; Kliszczewski et al, 1996;Maatje and Rossing, 1976;Maatje et al, 1992;McArthur et al, 1992;Ordolff, 2001). Despite great diagnostic possibilities, temperature methods are not presently fully utilised by milking systems producers.…”
Section: Introductionmentioning
confidence: 83%